The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s00253-015-7106-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bacterial and archaeal communities in depth-resolved zones in an LNAPL body

Abstract: Advances in our understanding of the microbial ecology at sites impacted by light non-aqueous phase liquids (LNAPLs) are needed to drive development of optimized bioremediation technologies, support longevity models, and develop culture-independent molecular tools. In this study, depth-resolved characterization of geochemical parameters and microbial communities was conducted for a shallow hydrocarbon-impacted aquifer. Four distinct zones were identified based on microbial community structure and geochemical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 73 publications
0
22
0
2
Order By: Relevance
“…The study was conducted at the same north‐central United States former refinery described in Sihota et al (in press), Irianni‐Renno et al (), Kiaalhosseini et al. (), McCoy et al (), Zeman et al (), and Akhbari ().…”
Section: Methodsmentioning
confidence: 99%
“…The study was conducted at the same north‐central United States former refinery described in Sihota et al (in press), Irianni‐Renno et al (), Kiaalhosseini et al. (), McCoy et al (), Zeman et al (), and Akhbari ().…”
Section: Methodsmentioning
confidence: 99%
“…A NSZD conceptual model, based on Irianni‐Renno et al (), and the combined body of work referenced in Table and Figure , is shown in Figure . Three distinct zones are defined here for their key role in the overall NSZD process.…”
Section: Nszd Conceptual Modelmentioning
confidence: 99%
“…But recent research indicates that syntrophic metabolism and methanogenesis can occur in more diverse geochemical environments than first thought. In their opinion article, Gieg et al () observe that syntrophic metabolism can sometimes occur even in the presence of electron acceptors, while Irianni‐Renno et al () describes concurrent sulfate reduction and methane production in the same zone based on data from multiple‐level sampling systems in an LNAPL area.…”
Section: Potential Controlling Factorsmentioning
confidence: 99%
“…Reds and browns are attributed to oxidized iron minerals. Grays and blacks are attributed to reduced metal sulfides associated with anaerobic degradation of petroleum hydrocarbons (Irianni Renno et al ).…”
Section: Resultsmentioning
confidence: 99%